Effects of Fine Gangue on Strength, Resistivity, and Microscopic Properties of Cemented Coal Gangue Backfill for Coal Mining - Tingye Qi; Guorui Feng; Yanrong Li; Yuxia Guo; Jun Guo; Yujiang Zhang (Shock and Vibration)
The cemented coal gangue backfill (CGB) in coal mining is normally made of gangue (particle size of 0–15 mm), fly ash, cement, and water. In this study, the effects of the weight content (ranging from 20% to 60%) of fine gangue (0–5 mm) on the microscopic characteristics, resistivity, and compressive strength of CGB were investigated at 3 d and 28 d curing times, respectively. The test results indicate that the strengths of the CGB, regardless of the curing time, increased with fine gangue content changing from 20% up to 40%. Further increase in fine gangue introduced a decrease in the strength. Another observation is that, at 3 days, a general increasing trend of CGB resistivity was noted with fine gangue content. At 28 days, the resistivity of CGB decreased with increase in the fine gangue content. Correlations between the resistivity and compression strength of CGB show a concave pattern, which attribute to the various micromechanism influenced on the resistivity and strength of CGB with different fine gangue content. It indicates that using resistivity to derive strength of CGB is not appropriate.